Evidence-based counseling and psychotherapy for an aging population - Glicken, Morley D. (Academic, 2009)
A compilation of evidence-based practices in the assessment and treatment of elderly clients. Focusing on the research and evidence regarding assessment, diagnosis, and treatment, it covers difficulties including: social isolation/loneliness, elder abuse/neglect, depression and suicidal inclinations, and patients with terminal illnesses